To Dare More Boldly : The Audacious Story of Political Risk - Hulsman, John C., 1967- (Book collections on Project MUSE., 2018)
Ten lessons from history on the dos and don'ts of analyzing political riskOur baffling new multipolar world grows ever more complex, desperately calling for new ways of thinking, particularly when it comes to political risk. To Dare More Boldly provides those ways, telling the story of the rise of political risk analysis, both as a discipline and a lucrative high-stakes industry that guides the strategic decisions of corporations and governments around the world. It assesses why recent predictions have gone so wrong and boldly puts forward ten analytical commandments that can stand the test of time. Written by one of the field's leading practitioners, this incisive book derives these indelible rules of the game from a wide-ranging and entertaining survey of world history. John Hulsman looks at examples as seemingly unconnected as the ancient Greeks and Romans, the Third Crusade, the Italian Renaissance, America's founders, Napoleon, the Battle of Gettysburg, the British Empire, the Kaiser's Germany, the breakup of the Beatles, Charles Manson, and Deng Xiaoping's China. Hulsman makes sense of yesterday's world, and in doing so provides an invaluable conceptual tool kit for navigating today's. To Dare More Boldly creatively explains why political risk analysis is vital for business and political leaders alike, and authoritatively establishes the analytical rules of thumb that practitioners need to do it effectively.